Daily new COVID-19 cases, the movement control order, and Malaysian stock market returns - Chia, Ricky Chee Jiun; Venus Khim-Sen Liew; Racquel Rowland (2020)
The Movement Control Order (MCO) not only restricts movement of human being, it also reduces firms’ financial profits and brings significant impact to stock returns. The objective of this study is to examine the relation between Malaysian stock market returns and variables related to the novel Coronavirus (COVID-19) pandemic outbreak. The FTSE Bursa Malaysia KLCI Index and eight selected main indices from 2 January 2020 to April 30, 2020, which includes the first three MCOs, are considered in this study. The results show that daily new confirmed COVID-19 cases and deaths had negative but insignificant impact on the returns on indices. Interestingly, MCO had significant and positive impact on all the indices’ returns while oversea financial risks had negative impact on these returns. Furthermore, it is found that the degree of impacts of MCO and oversea financial risks varied positively with the firm size of the indices’ constituent companies. China’s decision on unchanged loan prime rate on the 20 February 2020 was a favorable news to the Malaysia stock markets as indicated by the positive returns on all the indices. Similarly, the degree of impact of the China interest policy also varied positively with the firms’ characteristics. These findings are useful for investors in the Bursa Malaysia to manage their investment portfolios based on their appetites for risk.